2018
DOI: 10.3389/fpls.2018.00551
|View full text |Cite
|
Sign up to set email alerts
|

Patterning the Asteraceae Capitulum: Duplications and Differential Expression of the Flower Symmetry CYC2-Like Genes

Abstract: There are several types of capitulum in the Asteraceae due to different combinations of florets varying in corolla shape and stamen development. Previous studies have shown that the formation of ray florets on a radiate capitulum may be related to the parallel co-option of CYC2-like genes among independent Asteraceae lineages. The present work tests that hypothesis and attempts to shed light on the pattern of evolution of the Asteraceae capitulum and floral heteromorphism under the regulation of CYC2-like gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 62 publications
(112 reference statements)
4
77
1
2
Order By: Relevance
“…Presentan una amplia variación o plasticidad en el hábito de crecimiento, las características del vilano, el desarrollo de inflorescencias especializadas provistas de estructuras florales con presentación secundaria del polen que han coevolucionado directamente con sus diversos sistemas de cruzamiento y con sus mecanismos de polinización y dispersión (Panero & Funk, 2008;Panero et al, 2014), así como la producción de gran cantidad de metabolitos secundarios (Panero & Funk, 2008). Su radiación evolutiva fue impulsada por la arquitectura compleja del capítulo y sus transiciones adaptativas, en especial por la expansión y evolución de los genes de tipo CYC2 que contribuyen a su complejidad (Chen et al, 2018). Se destacan los procesos de poliploidización y diploidización que promueven el incremento de la tasa de especiación (Rivero-Guerra, 2008Rivero-Guerra & Laurin, 2012;Panero & Crozier, 2016).…”
Section: Asteraceae: Riqueza and Diversidadunclassified
“…Presentan una amplia variación o plasticidad en el hábito de crecimiento, las características del vilano, el desarrollo de inflorescencias especializadas provistas de estructuras florales con presentación secundaria del polen que han coevolucionado directamente con sus diversos sistemas de cruzamiento y con sus mecanismos de polinización y dispersión (Panero & Funk, 2008;Panero et al, 2014), así como la producción de gran cantidad de metabolitos secundarios (Panero & Funk, 2008). Su radiación evolutiva fue impulsada por la arquitectura compleja del capítulo y sus transiciones adaptativas, en especial por la expansión y evolución de los genes de tipo CYC2 que contribuyen a su complejidad (Chen et al, 2018). Se destacan los procesos de poliploidización y diploidización que promueven el incremento de la tasa de especiación (Rivero-Guerra, 2008Rivero-Guerra & Laurin, 2012;Panero & Crozier, 2016).…”
Section: Asteraceae: Riqueza and Diversidadunclassified
“…A distinct lineage has been estimated between H. annuus and H. radula (Schilling, Linder, Noyes, & Rieseberg, 1998;Timme, Simpson, & Linder, 2007), and these two species are very diversified with respect to plant architecture, life cycle and inflorescence form. However, in H. radula, the expression pattern of representative members of CYC2-like genes for pseudanthium development as HrCYC2c, HrCYC2d, and HrCYC2e in ray and disk flowers, was similar with respect to H. annuus (Chapman et al, 2008;Chapman et al, 2012;Chen et al, 2018). In fact, the transcript levels of HrCYC2c and HrCYC2d were very high in ray flower corolla but not in disk flowers, where transcripts were barely detectable ( Figure 7).…”
mentioning
confidence: 91%
“…(pseudanthium; Figure 1d) (for a review see Broholm, Teeri, & Elomaa, 2014). In radiate inflorescences, the ray flowers (pistillate or sterile) placed marginally (Figure 1d) enhance the ability to attract animal pollinators, thus increasing outcrossing and fitness while the inner and smaller disk flowers are fertile ( Figure 1d) (Chen, Shen, Guo, & Rao, 2018; Claßen-Bockhoff, 1990; Elomaa, Zhao, & Zhang, 2018).…”
mentioning
confidence: 99%
“…Because of transposon insertion of HaCYC2c in Helianthus annuus, the originally zygomorphic flat type of ray floret became the actinomorphic tubular type [21], while overexpression of RAY2 (CYC2 homologous gene) in Senecio vulgaris resulted in the formation of tubular type [22]. Studies of C. lavandulifolium, another ancestral diploid wild species of cultivated chrysanthemum [23], revealed that overexpression of CYC2c made the petal of ray floret longer than wild type [24], but ectopic expression of CYC2d hindered the growth of ray floret petals [25]. Previous studies have shown that the functions of CYC2 genes in ray florets of Asteraceae plants were quite different, which could not explain the reason for the formation of different ray floret types.…”
Section: Introductionmentioning
confidence: 99%